A SURVEY OF DEEP LEARNING MODEL FOR PROSTATE CANCER DIAGNOSIS - Izogie, L. E.; Akazue, M. I.; Ihama, E. I. (FUDMA Journal of Sciences, 2025)
Prostate cancer is one of the common types of cancer in men, and it is estimated that 1 out of 9 men will be diagnosed with prostate cancer at some point during their lifetime. AI techniques are being used to detect prostate cancer to improve accuracy and reduce costs, such as Machine Learning (ML) and Deep Learning (DL), which are used to analyze MRI scans and CT scans to analyze patient data such as age, race, family history, and lifestyle factors. The use of DL for prostate cancer detection can help reduce costs by reducing the need for expensive biopsies and other tests. This paper discussed different model and method used in predicting prostate cancer.